WORK MOTIVATION AND EMPLOYEE SATISFACTION IN ISLAMIC EDUCATION ORGANIZATIONS: CASE STUDY OF SMA DARUL MUKLASIN - Hafiduddin, M.; Baharun, Hasan; Lawal, Uthman Shehu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research analyses the relationship between work motivation and employee job satisfaction at Darul Muklasin High School. In Islamic educational institutions, work motivation, influenced by internal factors such as religious values, a sense of responsibility, and the awards received, plays a vital role in shaping job satisfaction. Job satisfaction, in turn, also strengthens employee motivation to work better. This research uses a qualitative approach with data collection techniques through in-depth interviews and participatory observation of Darul Muklasin High School employees. The research results show a mutually reinforcing positive relationship between work motivation and job satisfaction. Factors such as appropriate compensation, rewards for performance, a conducive work environment, and supportive leadership greatly influence these two aspects. Apart from that, work stress and high workload are obstacles that can reduce motivation and job satisfaction. Based on these findings, it is recommended that Darul Muklasin High School management increase compensation, create a more harmonious work environment, provide career development opportunities, and reduce work stress to increase employee motivation and job satisfaction. Implementing these recommendations is expected to improve employee performance and the overall quality of education at Darul Muklasin High School.